The Islamic Fortifications Project on Soqotra: Jebel Hawari Fort (SHP200) - Jansen van Rensburg, Julian; Cocca, Enzo; Demetrescu, Emanuel; Saeed Ahmed Al-Orqbi, Ahmed (Proceedings of the Seminar for Arabian Studies, 2023)
The first season of the Islamic Fortifications Project on Soqotra took place between the months of March and April 2022 in conjunction with GOAM Yemen and a team of local archaeologists from the Soqotra Heritage Project (SHP) The survey of the Islamic hillfort Jebel Hawari utilised an innovative methodological approach to generate a 3D model that helped rapidly capture the complexity of the stratigraphic archaeological record. Utilising this approach in conjunction with the historical and archaeological record has allowed us to propose four chronological and architectural phases that contrary to previous studies are wholly related to the Al-Mahrah stationed on Soqotra and not the Portuguese. While further work is ongoing the Islamic Fortification Project on Soqotra has allowed us a unique opportunity to further our understanding and knowledge of Soqotra’s Islamic period.